Depression in adolescence and young adulthood: the difficulty to integrate motivational/emotional systems - Giacolini, Teodosio; Alcaro, Antonio; Conversi, David; Tarsitani, Lorenzo (Frontiers in Psychology, 2025)
Depression is presented as a multi-factorial bio-psycho-social expression that has evolved primarily as an effect of stressors related to the motivational/emotional systems that regulate the BrainMind in our relationship with conspecifics. These stressors may be caused by two sources of threat, firstly, the loss of bonding with the caregiver and later with a partner and/or group which relates to the SEPARATION (PANIC/GRIEF) system, secondly, social defeat as an expression of the social competition and social dominance. The sexual maturity drives the individual to social competition and social dominance, even if the latter often occurs before sexual maturity, e.g., chickens, dogs, non-human primates, and humans. Depression is an evolutionarily conserved mechanism in mammals to terminate both separation anxiety, so as to protect the vulnerable social brain from the consequences of prolonged separation anxiety, and the stress of social competition when social defeat is predictable. Adolescence and Young adulthood are particularly susceptible to these two types of threat because of human developmental characteristics that are summarized by the term neoteny. This refers to the slowing down of growth and development, resulting in both a prolonged period of dependence on a caring/protective adult and the persistence of juvenile characteristics throughout life. Therefore, neoteny makes the transition from childhood to sexual maturity more dramatic, making the integration of the SEPARATION (PANIC/GRIEF) system with the dynamics of social competition and dominance more stressful and a source of depression. Stress is an expression of the HPA-Hypothalamic-Pituitary-Adrenal axis that articulates with other systems, mainly the autonomic nervous system and the immune-inflammatory system. The latter is believed to be one of the most significant components in the dynamics of depressive processes, connected to the prodromes of its activation in childhood, under the pressure of environmental and relational stressors which can lead to learned helplessness. The recurrence of stressors makes it easier for the immune-inflammatory system to be activated in later life, which could make a significant contribution to the establishment of a depressive disease. The possible contribution of children's identification processes with their parents' depressive personalities through observational learning is considered.